AVALIAÇÃO DE DIFERENTES TÉCNICAS DE OSTEOSSÍNTESE ILÍACA - Amaral, Bruna P.; Müller, Daniel C. d. M.; Serafini, Gabriele M. C.; Schossler, João E. W.; Spier, Jordana D. (Salão do Conhecimento, 2013)
Resumo